2016
DOI: 10.1902/jop.2015.150433
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Pathogens and Risk of Incident Cancer in Postmenopausal Females: The Buffalo OsteoPerio Study

Abstract: Background Extraoral translocation of oral bacteria may contribute to associations between periodontal disease and cancer. The associations among the presence of three orange-complex periodontal pathogens (Fusobacterium nucleatum, Prevotella intermedia, and Campylobacter rectus), two red-complex periodontal pathogens (Porphyromonas gingivalis and Tannerella forsythia), and cancer risk were investigated. Methods A total of 1,252 postmenopausal females enrolled in the Buffalo Osteoporosis and Periodontal Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 46 publications
0
55
2
1
Order By: Relevance
“…So, the interpretation of the OR value should be made with extreme caution. The absence of a strong association between the presence of some bacteria and cancer was confirmed also by a paper published in 2016 reporting the result of a prospective study on postmenopausal women [ 57 ].…”
Section: Discussionmentioning
confidence: 74%
“…So, the interpretation of the OR value should be made with extreme caution. The absence of a strong association between the presence of some bacteria and cancer was confirmed also by a paper published in 2016 reporting the result of a prospective study on postmenopausal women [ 57 ].…”
Section: Discussionmentioning
confidence: 74%
“…Prevotella species are Gram-negative, anaerobic bacteria which belong in the phylum Bacteriodetes . Although in healthy humans the Prevotella genus is one of the dominant genera of the salivary microbiome, distinct members of the genus Prevotella are associated with inflammatory diseases and may facilitate carcinogenesis as well [ 86 - 88 , reviewed by 89 , 90 ]. There are, however, contradicting observations regarding the role of Prevotella in the development of oral cancer [ 14 , 74 , 79 , 91 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). To our knowledge, only two epidemiological studies of this type have suggested [155] or showed [156] this direct relationship between periodontitis and cancer. If that relationship could be confirmed, oral hygiene might be a safer and easier approach to prevent CRC and probably other cancers and diseases, as it has been already suggested [157] .…”
Section: Resultsmentioning
confidence: 99%